In vivo localization of occult lesions and margins in breast carcinoma using radio-fluorescence: a new hybrid technique - Pereira, Antônio César; Moriguchi, Sonia Marta; Dutra, Mara Costa; Ferreira, Rogério Bizinoto; Jesus, Alexandre Marchiori Xavier de; Conde, Délio Marques; Pinto, Sebastião Alves; Beingolea, Jorge Rodolfo (Mastology, 2024)
Objective: The aim of this study was to present a new technique for hybrid marking of non-palpable breast lesions and in vivo evaluation of surgical margins, called Fluorescence and Seed for Hybrid Intraoperative Evaluation. Methods: Seven women with non-palpable breast lesions and suspected or confirmed malignancy underwent prior iodine-125 seed implantation and peripheral intravenous administration of indocyanine green 30 min before surgery. A hybrid gamma probe with an optonuclear probe was used to detect gamma radiation in the lesions and, sequentially, the fluorescence mode, in the same lesion and its margins, after its removal. Results: This method distinguished, in real time, one benign and six malignant lesions, guiding the removal, identifying the remaining neoplastic area in the surgical bed, and allowing its intraoperative enlargement. Conclusion: This pilot study evaluates the feasibility of this new technique in identifying the primary lesion and controlling surgical margins using hybrid technology.